Molecular characterization of threshability genes in wheat - Sood, Shilpa (Kansas State University, 2008)
Threshability is an important agronomic trait in wheat as free-threshing forms facilitate mechanical threshing of grain. All wild relatives of wheat have tough glumes and are non-free-threshing, whereas most cultivated wheats have soft glumes and are free-threshing. Two genetic loci are known to govern the threshability trait in bread wheat. The Q gene located on chromosome 5AL and glume tenacity genes located on homoeologous group-2 chromosomes seem to interact to produce a free-threshing phenotype. Although, the Q gene was found to be a member of APETALLA 2 (AP2) class of transcription factors, the molecular nature of the tough glume genes remains unknown. In the present study, genetic and molecular characterization of two of the threshability genes in wheat was undertaken. The soft glume (sog) gene of diploid wheat and tenacious glume (Tg) gene of hexaploid wheat were characterized and mapped on short arm of chromosome 2Am and 2D respectively. Comparative mapping of sog and Tg genes suggested their independent origins. The sog gene was mapped in a low-recombination region near the centromere on 2AmS. Genomic targeting using deletion bin mapped ESTs assigned the Tg gene to a 4.9 cM interval in the distal 16% of short arm of chromosome 2D. In order to find additional markers for fine-mapping the Tg gene, macrocolinearity between rice and wheat was explored in the Tg region. Although synteny between rice and wheat was found to be conserved in the distal region of chromosome 2DS, the genomic region encompassing the Tg gene in wheat showed some rearrangements relative to rice. Molecular characterization of ethyl methanesulfonate-induced free-threshing mutants in two different non-free-threshing backgrounds revealed point mutations as well as variable sized deletions at Tg locus. Targeting of Tg to the high-recombination gene-rich region in wheat and availability of several genomic resources from the present study will aid in the cloning and further characterization of this important agronomic gene.
Keywords: Domestication; Threshability; Wheat; Molecular mapping; Biology, Genetics (0369)